(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study investigates the challenges Uzbek learners face in acquiring the English verb ‘to be’, focusing on structural differences between Uzbek and English copula expression. In Uzbek, the copula is consistently marked through suffixes in first and second person forms, a long dash in third-person nouns, and morphological integration in adjectives, while negative and interrogative sentences use suffixes -mas and -mi. In contrast, English requires a separate, inflected verb that changes according to person and number. These differences often lead to errors in subject-verb agreement, omission or misuse of forms, and difficulties with negative and interrogative constructions. The study analyzes these patterns through comparative linguistic analysis and proposes targeted teaching strategies, including explicit contrastive instruction, structured drills, and contextualized communicative practice, to improve learners’ grammatical accuracy and confidence in using ‘to be’ in English.